(untitled) (Research, Society and Development, 2020)
This article aims to present operations with fractions, a constant issue in Basic Education, through activity proposals using comics for a differentiated approach to the theme.The educational comics aim to overcome the difficulties that students have in basic fractions operations and also promote the reinvention of teaching practices and take advantage of the potential of comics.We used a qualitative methodology of a descriptive nature that resulted in the construction of two didactic proposals. The first proposal promotes initial provocations to mobilize previous knowledge. The second proposal presents square representations of the addition and subtraction of fractions. So our study proposes to teachers a practical guide to orientate them in their educational practices, in order to familiarize them with the resource of comics, being able to adapt them to achieve their goals, time and audience. In this perspective, it is understood that the practice with comics can be incorporated into mathematics classes, as well, with it, the idea of sub-reading is demystified, so that, thus, there is awareness and familiarization with language, promoting a significant formative perspective in the performance of the teaching profession in the teaching of Basic Education.